In vitro antifungal activity of recombinant chitinase protein against Corynespora cassiicola infecting Hevea brasiliensis - Philip S; Abraham A; Joseph A; Prem E; Sathik M B M; Thomas K U (Rubber Science, 2015)
Corynespora leaf disease caused by Corynespora cassiicola has emerged as a major disease of rubber in South East Asia. During plant-pathogen interactions, various novel proteins called pathogenesis related (PR) proteins which play a major role in plant disease resistance mechanism are induced. The chitinase (PR3) is one of the most widely studied groups of PR proteins in plants. C.cassiicola induced chitinase from Hevea brasiliensis was characterised in the present study. The cDNA was developed from the RNA of C. cassiicola infected leaves of the clone GT 1. A 978 bp chitinase gene was obtained from H. brasiliensis and over expressed in the pET 32a+ expression system. The in vitro studies of purified recombinant Hevea chitinase showed antifungal activity against C. cassiicola. The chitinase gene expression in H. brasiliensis during C. cassiicola infection was quantified through qPCR and increased expression of chitinase transcripts was observed. In clone GT 1 chitinase gene was induced up to 24th hour after C.cassiicola infection and eventually it came down in later hours, where as in clone RRII 105 chitinase level had been lesser in induced plants than control. The polyclonal antibody was raised with the recombinant chitinase and the induced clone GT 1 showed a prominant band in western blot, while a minor band was observed in RRII 105 in induced condition.
Keywords: Chitinase; Corynespora cassiicola; Hevea brasiliensis; Recombinant protein